2018
DOI: 10.3389/fphys.2018.01738
|View full text |Cite
|
Sign up to set email alerts
|

Effects of High-Intensity Interval Training vs. Sprint Interval Training on Anthropometric Measures and Cardiorespiratory Fitness in Healthy Young Women

Abstract: Purpose: To compare the effects of 8 weeks of two types of interval training, Sprint Interval Training (SIT) and High-Intensity Interval Training (HIIT), on anthropometric measures and cardiorespiratory fitness in healthy young women.Methods: A randomized clinical trial in which 49 young active women [age, 30.4 ± 6.1 years; body mass index, 24.8 ± 3.1 kg.m−2; peak oxygen consumption (VO2peak), 34.9±7.5 mL.kg−1.min−1] were randomly allocated into a SIT or HIIT group. The SIT group performed four bouts of 30 s a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 56 publications
0
37
0
2
Order By: Relevance
“…A study on abdominal, iliac crest, biceps, triceps, subscapular, calf and thigh skinfolds of non-athletes showed the highest score in thigh following by iliac crest [44]. Moreover, a research on triceps, subscapular, suprailiac, abdominal and thigh skinfolds found thigh as the largest one as well [45]. Furthermore, an examination of triceps, subscapular, biceps, iliac crest, suprailiac, abdominal, front thigh and medial calf showed front thigh as the largest one followed by abdominal [46].…”
Section: Discussionmentioning
confidence: 96%
“…A study on abdominal, iliac crest, biceps, triceps, subscapular, calf and thigh skinfolds of non-athletes showed the highest score in thigh following by iliac crest [44]. Moreover, a research on triceps, subscapular, suprailiac, abdominal and thigh skinfolds found thigh as the largest one as well [45]. Furthermore, an examination of triceps, subscapular, biceps, iliac crest, suprailiac, abdominal, front thigh and medial calf showed front thigh as the largest one followed by abdominal [46].…”
Section: Discussionmentioning
confidence: 96%
“…Exercise has significant improvement in VO2 max. 20 Regular exercise done by healthy sedentary and active adults show an improvement of their VO2 max. 21 This study was limited by the absence of daily physical activity and waist circumference data.…”
Section: Discussionmentioning
confidence: 98%
“…In a recent article published by our group [6], 49 women were randomly assigned to perform two types of interval training (IT), high-intensity interval training (HIIT) and sprint interval training (SIT), and found positive changes in their adiposity measures (assessed by the sum of skinfolds) without changing their nutritional habits (assessed by 24-h dietary recalls). Here, we further explore if the results obtained were related to the nutritional changes.…”
Section: Current Support For Exercisementioning
confidence: 99%